On the Evidential Burden of Causation in Civil Lawsuit of Environmental Pollution for Public Interests Review and Improvement - Cong, Jia (International Journal of Social Sciences and Public Administration, 2024)
In order to compensate for the original litigation's inability to adequately address an extensive variety of environmental issues, civil lawsuit of environmental pollution for public interests is essential for safeguarding the ecological balance and averting possible environmental risks. It supports the protection of society's interest in the environment and the realization of environmental rights. Building a flawless causation proof of the applicable system is essential since the proof of causation is a crucial component in civil lawsuit of environmental pollution for public interests, which did not find any express provisions.In actuality, the judge's primary challenge in determining causality distribution is applying proof of causation. The burden of proof was distributed without regard to the purpose of the proof, and proof of responsibility did not differentiate between the many subjects of the ability to prove. Thus, it is necessary to first define the burden of evidence standard as well as the value orientation of environmental civil public benefit lawsuit. It also highlights the issue of shifting the evidential burden for causality in the other direction. It clarifies which standards of proof to use when the Procuratorate and social organizations are the plaintiffs. By more evenly allocating the evidential burden for causation, civil lawsuit of environmental pollution for public interests will become more value-oriented.